Overview Of The Husband's Level Of Knowledge About Sexual Intercourse During Pregnancy Third Trimester At BPM Sri Lumintu - Ratih Prananingrum; Suryo Ediyono (CV. Inara, 2022)
Background: A father-to-be will be very concerned about the condition of pregnant women and avoid sex for fear of injuring the baby. The results of a preliminary study at BPM Sri Lumintu conducted interviews with 10 husbands who drove pregnant wives to the third trimester obtained data that 4 husbands had sex feeling worried and anxious, 3 husbands had decreased, and 3 husbands did not have intercourse because they were afraid of the condition of the fetus. Purpose: knowing the picture of the husband's level of knowledge about sexual intercourse during the third trimester of pregnancy. Methods: Descriptive research methods, longitudinal time approaches and accidental sampling techniques of the study population of 45 people sampled 33 respondents. Pearson product moment validity test and α-Cronbach reliability test. Results: the husband's level of knowledge about sexual intercourse during pregnancy trimester III is sufficient (42.2%), Good needs (55.6%), problems are sufficient and less (37.8%), attitude changes are less (37.8%), moderate activity (51.1%), good position (55.6%)